A Geografia segundo Élisée Reclus: as diferenças entre as metodologias tradicional e libertária no ensino de geografia - Pantarotto, Théo Leandro de Sousa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research is based on the libertarian model of the teaching of geography, having the french geographer anarchist Élisée Reclus as a base of thinking. He participated of some insurrections which the main one was the Comuna de Paris. This geographer didn't use the geographic division between human and physics, his geographic conception was totalizing, and created the concept of social geography, which is used until now (21st century). This geography thought which Reclus believed(libertarian) antagonized with some others, and the geographer anarchist used to say that the creators of the other thoughts were linked with the State and they didn't want the progress of the science. In Reclus's book 'Education', he systematized the libertarian pedagogy, which the education, as a whole, should be. This research is ended showing the methodology adopted in the teaching of geography, used by Reclus (libertarian), and also the teachingof geography today, in the 21st century, showing the differences between them

Este trabalho se fundamenta no ensino de geografia nos moldes libertários tendo como base o anarquista geógrafo ÉliséeReclus, que nasceu na França e participou de algumas insurreições, da qual a principal delas foi a Comuna de Paris, este geógrafo não utilizava a separação da geografia entre humana e física, sua concepção geográfica era totalizante e criou o conceito de geografia social, que é utilizada até hoje (século XXI). A corrente geográfica da qual Reclus fez parte (libertária), antagonizava com algumas outras, que o anarquista geógrafo dizia que os idealizadores dessas outras correntes estavam ligados ao Estado e não queriam o progresso da ciência. Reclus em seu livro Educação,sistematizou toda a pedagogia libertária, o que a educação, como um todo, deveria ser. O trabalho é finalizado mostrando a metodologia adotada no ensino de geografia adotada por Reclus (libertária) e também o ensino de geografia atual, do século XXI e mostrando as diferenças entre eles
Keywords: Geografia - Estudo e ensino; Geografia - Metodologia; Anarquismo e anarquistas